Hypofractionated Irradiation Has Immune Stimulatory Potential and Induces a Timely Restricted Infiltration of Immune Cells in Colon Cancer Tumors - Frey, Benjamin; Rückert, Michael; Weber, Julia; Mayr, Xaver; Derer, Anja; Lotter, Michael; Bert, Christoph; Rödel, Franz; Fietkau, Rainer; Gaipl, Udo S. (Frontiers in Immunology, 2017)
In addition to locally control the tumor, hypofractionated radiotherapy (RT) aims particularly to activate immune cells in the RT-modified microenvironment. Therefore we examined, whether hypofractionated RT can activate dendritic cells (DCs), induce immune cell infiltration in tumors and how the chronology of immune cell migration into tumors occurs to gain knowledge for future definition of radiation breaks and inclusion of immunotherapy. Colorectal cancer treatments offer only limited survival benefit and immunobiological principles for additional therapies need to be explored with pre-clinical models. The impact of hypofractionated RT on CT26 colon cancer tumor cell death, migration of DCs towards supernatants (SN) and activation of DCs by SN was analyzed. The subcutaneous tumor of a BALB/c-CT26 mouse model was locally irradiated with 2x5Gy, the tumor volume was monitored and the infiltration of immune cells in the tumor was determined by flow cytometry daily. Hypofractionated RT induced a mixture of apoptotic and necrotic CT26 cells which is known to be in particular immunogenic. DCs that migrated towards supernatants of CT26 cells only upregulated the activation markers CD80 and CD86 when in contact with SN of irradiated tumor cells. After hypofractionated RT the tumor outgrowth was significantly retarded and in the irradiated tumors an increased infiltration of macrophages (CD11bhigh/F4-80+) and DCs (MHC-II+), but only between day 5 and 10 after the first irradiation takes place. While CD4+ T cells migrated into non-irradiated and irradiated tumors, CD8+ T cells were only found in tumors that had been irradiated and they were highly increased at day 8 after the first irradiation. Myeloid-derived suppressor cells and regulatory T cells show regular turnover in irradiated and non-irradiated tumors. Tumor cell-specific anti-IgM antibodies were enhanced in the serum of animals with irradiated tumors. We conclude that hypofractionated RT suffices to activate DCs and to induce infiltration of innate and adaptive immune cells into solid colorectal tumors. However, the presence of immune cells in the tumor which are beneficial for anti-tumor immune responses is timely restricted. These findings should be considered when innovative multimodal tumor treatment protocols of distinct RT with immune therapies are designed and clinically implemented.